Organization Transparency and Public Service Quality During Pandemic - Suasa, Suasa; Mappatoba, Mustainah; Samad, Muhammad Ahsan (Political Science Program, Universitas Negeri Semarang, 2023)
The paper aims to test a theoretical model that states the effect of organizational transparency and negative emotions on the quality of service in handling COVID-19. The study focuses on Palu City Social Service and Health Service as government organizations that have contributed most to handling the COVID-19 pandemic in serving public needs.. Research methods used in this study include descriptive data analysis, bivariate correlation, confirmatory factor analysis (CFA), and regression . The study also involves a theoretical model that tests the effect of organizational transparency and negative emotions on the quality of service in handling COVID-19. Overall, this article uses a combination of quantitative research methods to analyze the impact of organizational transparency on public service quality during a crisis like COVID-19.The study found that transparency has a significant positive impact on service quality in handling COVID-19. The analysis indicates that the handling of COVID-19 in Palu City is in accordance with the policies set by the central government and local governments.